(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article examines the didactic principles that ensure the effective development of sociolinguistic competence in language education. Sociolinguistic competence is understood as the ability to choose and use linguistic forms appropriately according to the social context, communicative purpose, status of interlocutors, and cultural norms. In modern education, this competence is considered an essential component of communicative competence because successful communication depends not only on grammatical accuracy, but also on the socially appropriate use of language. The study is based on theoretical analysis of pedagogical, linguistic, and methodological literature. The article systematizes major didactic principles that support the formation of sociolinguistic competence, including communicative orientation, contextuality, cultural relevance, learner-centeredness, authenticity, interactivity, and reflexivity. The research argues that these principles should be implemented in an integrated way through situational tasks, authentic materials, dialogic learning, and reflective practice. The findings show that sociolinguistic competence develops most effectively when language learning is connected with real-life communication and when students are guided to understand the relationship between language, society, and culture. The article concludes that the observance of didactic principles in the educational process contributes to the formation of flexible, culturally sensitive, and socially responsible language users.